Sexuality in China : histories of power & pleasure - Chiang, Howard, 1983- (Seattle : University of Washington Press, 2018)
What was sex like in China, from imperial times through the post-Mao era? The answer depends, of course, on who was having sex, where they were located in time and place, and what kind of familial, social, and political structures they participated in. This collection offers a variety of perspectives by addressing diverse topics such as polygamy, pornography, free love, eugenics, sexology, crimes of passion, homosexuality, intersexuality, transsexuality, masculine anxiety, sex work, and HIV/AIDS. Following a loose chronological sequence, the chapters examine revealing historical moments in which human desire and power dynamics came into play. Collectively, the contributors undertake a necessary historiographic intervention by reconsidering Western categorizations and exploring Chinese understandings of sexuality and erotic orientation.
Introduction: writing the history of sexuality in China -- Polygyny and its discontents: a key to understanding traditional Chinese society -- Between topics and sources: researching the history of sexuality in Imperial China -- The pornographic doctrine of a loyalist Ming novel: social decline and sexual disorder in preposterous words (Guwangyan) -- Bertrand Russell and Ellen Key in China: individualism, free love, and eugenics in the May Fourth era -- "A problem of glands and secretions": female criminality, murder, and sexuality in Republican China -- Changing sex in the urban press: scientific modernity and the shaping of transsexual subjects in twentieth-century China -- A reparative return to "queer socialism": male same-sex desire in the cultural revolution -- The irony of size: male smallness and the rise of China -- Sex and work: HIV/AIDS and elite masculinity in contemporary China -- Glossary of Chinese characters -- Bibliography -- Index.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 17, 2018).
JSTOR
Keywords: Sex -- China -- History; Sex customs -- China -- History; Sexualité -- Chine -- Histoire; Vie sexuelle -- Chine -- Histoire; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; HISTORY / Asia / China; Sex; Sex customs; China; Sexualverhalten; China; History; Aufsatzsammlung